Pengaruh Model Student Teams Achievement Division (STAD) dengan Media Video terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas XI SMA UISU Medan - Nurhalimah Sibuea (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
The study population was all grade XI students North UISU senior High School, totaling 70 people, While the research class XI Science and Social Sciences, which compares two classes where class XI Science as an Experiment class uses the learning model of Student Teams Achievement Division (STAD) with media in the form of video and social science class as a class control without using the learning model Student Teams Achievement Division (STAD) using video media. Experiment obtained the value Lhitung < Ltable (0.88 < 0.137) proves that the variable X data is normally distributed. in the Control class ,the value of that Lhitung < Ltable (0.97 < 0.161) proves that the variable Y data is normally distributed. Based on homogeneity that has been done, then (1.4 < 3.98). This proves that the sample of researchers comes from a homogeneous population. Value of t(table) = 1.99 with t_count = 9.26. then the alternative hypothesis is accepted it can be concluded that the learning model of Student Teams Achievement Division (STAD) with media in the form of video has a significant effect in increasing the ability to write explanatory texts.